PERAN WANITA DALAM NOVEL TENAGA KERJA ISTIMEWA KARYA NAIQUEEN - Febrianti, Rizki; Isani Kulup, Luluk (Universitas PGRI Adi Buana Surabaya, 2019)
The background of this research is the fact that the study of feminism that can deliver on a trueunderstanding of gender. The studies are often used to understand gender issues are studies in thesocial sciences. Of the various social assessment is emerging theories are then used as the theoriesof gender or sometimes called theories of feminism. In a broad sense is a movement feministwomen to reject everything that is lowered by a culture dominated by men. The object of this studyare excerpts novel that tells the story of Indonesian Workers who work as waiters obliged obeyorders from his master who would flip over the main character lives. Based on the results penilitiancan be concluded that the novel Labor Naiqueen Outstanding works are some quotes about liberalfeminism. And according to Naomi Wolf defines feminism as a theory that reveals the personaldignity and the dignity of all women. In this novel there are three things among other things: thesuppression in the field of work, oppression in the field of marriage, and in the field of genderoppression.